Multimodal Literacy and Linguistic Landscape: A Digital Tandem Project in European Teacher Education - Edina Krompák; Esa Hartmann (ALSIC: Apprentissage des Langues et Systèmes d'Information et de Communication)
This study investigated student teachers' reflections on the pedagogical affordances of digital media and digital citizenship education in the context of language teaching and learning in multilingual classrooms. The project Multimodal Literacy and Linguistic Landscape was carried out jointly in Switzerland and France to explore the novel interconnection between multimodal literacy and linguistic landscape research in the context of digital citizenship education. The purpose of this project was to carry out a digital exchange between student teachers of the two universities, in order to create several multimodal storytelling performances using digital media. These interactive digital storytelling performances were based on a selection of Tomi Ungerer's picturebooks and presented to preschool and primary classes in the two countries, with the aim of promoting pluriliteracy as part of digital citizenship education. The investigation was guided by the following research questions: What are the effects of the international digital exchange on student teachers' attitudes and beliefs towards creative and multimodal pedagogical approaches? What are the impacts of this intercultural exchange on their multimodal performances, as well as their linguistic, cultural and professional identities? How can digital citizenship education be implemented in language teaching and learning in multilingual classrooms and in multilingual teacher education at university?